Fostering a Love for Arabic through Digital Media: Developing a Communicative Dictionary Prototype for Islamic Elementary School Students - Ahmad Syadzili; Mohammad Ahsanuddin; Moch. Wahib Dariyadi (Al-Wazan: Journal of Arabic Education, 2026)
The low interest of Madrasah Ibtidaiyah (Islamic Elementary School) students in learning Arabic often stems from the use of static and non-functional learning media. This research aims to develop a communicative digital dictionary prototype specifically designed to foster an early affinity for the Arabic language, aligned with the "Love-Based Curriculum" (Kurikulum Berbasis Cinta or KBC) initiated by the Ministry of Religious Affairs. The study employs the Research and Development (R&D) method, adopting the ADDIE model, which is limited to the analysis, design, and development stages. The resulting product is the "Arabi-Fun" interactive dictionary application prototype, which integrates multimedia features such as native speaker audio, iconic visualizations, and functional sentence scenarios. The development results detail the technical specifications of the prototype, which incorporates deep learning principles through the pillars of mindful, meaningful, and joyful learning. The integration of the Panca Cinta (Five Pillars of Love) concept within this medium aims to reduce students' cognitive load and affective filters while simultaneously instilling a love for knowledge and spiritual values. This prototype is expected to serve as a strategic instrument in transforming madrasah education to be more humanistic, adaptive, and digitally literate in the Society 5.0 era.